2008
DOI: 10.1021/ie8002045
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel from Low-Grade Animal Fat: Production Process Assessment and Biodiesel Properties Characterization

Abstract: Biodiesel from different mixtures of animal fat and soybean oil has been synthesized, and its properties have been evaluated and related to its composition. A mixture of 50 vol % of both raw materials has been selected as a suitable feedstock for industrial biodiesel production, and a computer simulation of the production process using Aspen Plus software has been carried out to evaluate the industrial feasibility of this scheme using this cheaper feedstock. The results obtained suggest that the process propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(61 citation statements)
references
References 44 publications
1
59
0
1
Order By: Relevance
“…Meanwhile [7] simulated four continuous processes using HYSYS and waste vegetable oils alone under homogenous and heterogeneous catalysis, they concluded that the heterogeneous acid catalyst process was more beneficial. Reference [25] presented a process for obtaining biodiesel from low-grade animal fats. Other simulation studies that have been carried out have utilized solid resin-catalyzed transesterification [26], enzyme catalysis [27][28] and supercritical conditions [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile [7] simulated four continuous processes using HYSYS and waste vegetable oils alone under homogenous and heterogeneous catalysis, they concluded that the heterogeneous acid catalyst process was more beneficial. Reference [25] presented a process for obtaining biodiesel from low-grade animal fats. Other simulation studies that have been carried out have utilized solid resin-catalyzed transesterification [26], enzyme catalysis [27][28] and supercritical conditions [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Animal fats and vegetable oils have been widely used as alternative feedstocks for biodiesel production in order to reduce the dependence on fossil-fuel-based diesel [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. To increase usage of these feedstocks, much attention has been paid to its use in the production of diesel-like fuels and/or other value-added chemicals [15].…”
Section: Introductionmentioning
confidence: 99%
“…Reddy et al 12 showed that nanocrystalline CaO as heterogeneous catalyst required 6 h for the maximum conversion of fat into biodiesel. Canoria et al 13 investigated the production of biodiesel from mixtures of animal fat and soybean oil in two stages. In first stage, esterification was carried out with p-toluenesulfonic acid followed by transesterification with methanol using sodium methoxide as catalyst.…”
Section: Introductionmentioning
confidence: 99%